Theoretical Foundations of the Development of Modern Civil Society Institutions in a Democratic Legal State - Batirovich, Masharipov Ikramjon (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The management of the state and society is complex and various management models and forms of management have been developed, the process of building a modern civil society, certain specific features have been analyzed, as well as effective cooperation between non-governmental non-commercial organizations, political parties, self-government bodies and state local authorities. based on increasing the level, development of civil society institutions and ensuring their independence from state bodies, the author's comments on full-fledged management were formed.